Early brain metastasis of advanced gastric cancer with a pathological complete response to neoadjuvant chemotherapy followed by surgery: A case report and literature review. Issue 10 (3rd October 2018) - Luo, Hui; Peng, Liangqun; Wang, Nan; Zhang, Jiangong; Zheng, Xiaoli; Sun, Yanan; Fan, Chengcheng; Ge, Hong
ABSTRACT: Advanced gastric cancer with a pathological complete response to neoadjuvant chemotherapy and surgery followed by early brain metastasis is rare. A 52-y-old male patient who was diagnosed with advanced gastric cancer (cT4N2M0, stage ШB). Radiological examinations after three cycles of preoperative chemotherapy with a modified FOLFOX6 (mFOLFOX6) regimen showed a partial response (PR) had been achieved. The patient underwent curative surgery consisting of proximal gastrectomy, and D2 lymph node dissection. The lack of abnormal gastric cancer cells in the primary lesion or lymph nodes confirmed a pathological complete response (pCR). Postoperative chemotherapy with oral S-1 was administrated. However, during the second cycles of postoperative chemotherapy, the patient experienced headaches, projectile vomiting and convulsion. Upon further examination, a tumor representing metastasis to the brain was recognized by cranial enhanced magnetic resonance imaging (MRI) examination and cytopathology of cerebrospinal fluid. In addition to documenting the case report, we reviewed the literature associated to features of metastatic brain malignancies that form from gastric cancer. In short, advanced gastric cancer patents achieved pCR after preoperative chemotherapy typically have good prognosis; however, great attention should be paid on detecting metastatic events.